2017
DOI: 10.1002/ls.1379
|View full text |Cite
|
Sign up to set email alerts
|

Ferrofluid lubrication of finite journal bearings using Jenkins model

Abstract: The present study investigates hydrodynamic lubrication by ferrofluids of finite journal bearings using the Jenkins model. A magnetic field created by displaced finite wire is used. A numerical solution for the modified Reynolds equation using the finite difference method is obtained. Static characteristics of finite journal bearings are analyzed using 2 control parameters: magnetic force coefficient and Jenkins viscosity. The obtained results are compared to those from Neurenger‐Rosensweig model. It is shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Most of engine bearings are hydrodynamic journal bearings. The following are some recent references [4–13] of different journal bearings from different viewpoints using FFs as lubricant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of engine bearings are hydrodynamic journal bearings. The following are some recent references [4–13] of different journal bearings from different viewpoints using FFs as lubricant.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that dimensionless load‐carrying capacity increases with the increase of squeeze parameter, cohesion force coefficient and couple stress parameter of the MF. Laghrabli et al [10] studied finite journal bearings, where a magnetic field is created by displaced finite wire. The results show the increase in pressure, load capacity, attitude angle and side leakage while decrease in friction factor when the value of each control parameter (magnetic force coefficient and viscosity) increased at low and medium eccentricity ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, proper rotation of ferromagnetic particles within the carrier base fluid in the presence of magnetic fields affects the fluid viscosity and thus the journal bearing characteristics. Laghrabli et al [19,20] investigated the influence of ferromagnetic particles rotation on the static behavior of finite journal bearing operating with ferrofluids under the effect of a magnetic field generated by a finite wire. Using both Shliomis and Jenkins models, these authors calculated the journal bearing static characteristics and they confirmed that the use of magnetic fluids, compared to Newtonian ones, increases de pressure and consequently the load carrying capacity of the journal bearing.…”
Section: Introductionmentioning
confidence: 99%
“…This locally changes the effective viscosity, locally changing the resistance of the lubricant transportation. In addition, often these effects are accompanied by an attracting force between the fluid and the field, giving rise to an extra body force in the lubrication layer (Laghrabli et al, 2017a(Laghrabli et al, , 2017b. In general, it can be said that locally changing this rheological behaviour has similar effects as locally changing the geometry of the bearing van Ostayen, 2017a, 2017b).…”
Section: Introductionmentioning
confidence: 99%